Outcome of endodontic micro-resurgery: A systematic review - Faisal Alnassar; Riyadh Alroomy; Qamar Hashem; Abdullah Alqedairi; Nabeel Almotairy (Saudi Endodontic Journal)
Introduction: Endodontic micro-resurgery is a procedure that is performed in cases where previous surgical treatments have not been successful. However, the treatment outcomes of this approach remain unclear. This systematic review aimed to evaluate the treatment outcomes of endodontic microresurgery in studies that utilized microsurgical techniques and biocompatible root-end filling materials. In addition, the reason for failure of the primary treatment was evaluated. Materials and Methods: A systematic search was conducted across five databases: PubMed, Web of Science Core Collection, and EBSCO host (MEDLINE, Academic Search Ultimate, and ERIC), up to April 24, 2023. Only studies on living humans with endodontic micro-resurgery outcomes were included. The Joanna Briggs Institute tools were used to critically assess the included studies for quality and bias. Results: Four studies were included in the review (one prospective, one retrospective, and two case reports/series). The risk of bias was moderate in two studies and high in the other two. The total number of patients in the included studies was 142, with a diverse age distribution ranging from 21 to > 60 years. In total, 148 permanent teeth (anterior, premolar, and molar) across the studies underwent endodontic micro-resurgery. The reported success rates varied between 87.6% and 92.9%, except for one high-bias study with a significantly lower rate (75%). Conclusions: The absence of root-end filling and missed canals are the main reasons why primary endodontic microsurgeries often fail. Endodontic micro-resurgery remains a viable treatment option for failed primary endodontic microsurgery. However, further research is needed on this topic.